WebFRIS: An efficient web-based decision support tool to disseminate end-to-end risk information for flood management - Mohanty, Mohit Prakash; Karmakar, Subhankar (Journal of Environmental Management, 2021)

Assessment of socio-economic strategies for managing regional flood risk in an urban coastal catchment - Ghosh, Mousumi; Ghosh, Subimal; Karmakar, Subhankar (Urban Climate, 2024)

Flood management in India: A focussed review on the current status and future challenges - Mohanty, Mohit Prakash; Mudgil, Sahil; Karmakar, Subhankar (International Journal of Disaster Risk Reduction, 2020)

Tide-rainfall flood quotient: an incisive measure of comprehending a region’s response to storm-tide and pluvial flooding - Mohanty, Mohit Prakash; Sherly, Mazhuvanchery Avarachen; Ghosh, Subimal; Karmakar, Subhankar (Environmental Research Letters, 2020)
Abstract It is undeniable that coastal regions worldwide are facing unprecedented damages from catastrophic floods attributable to storm-tide (tidal) and extreme rainfall (pluvial). For flood-risk assessment, although recognizing compound impact of these drivers is a conventional practice, the marginal/individual impacts cannot be overlooked. In this letter, we propose a new measure, Tide-Rainfall Flood Quotient (TRFQ), to quantify the driver-specific flood potential of a coastal region arising from storm-tide or rainfall. A set of inundation and hazard maps are derived through a series of numerical and hydrodynamic flood model simulations comprising of design rainfall and design storm-tide. These experiments are demonstrated on three different geographically diverse flood-affected coastal regions in India. The new measure throws light on existing knowledge gaps on the propensity of coastal flooding induced by the marginal/individual contribution of storm-tide and rainfall. It shall prove useful in rationalizing long-term flood management strategies customizable for storm-tide and pluvial dominated global coastal regions.

Quantifying flood risks during monsoon and post-monsoon seasons: An integrated framework for resource-constrained coastal regions - Thakur, Dev Anand; Mohanty, Mohit Prakash; Mishra, Ashok; Karmakar, Subhankar (Journal of Hydrology, 2024)